2006
DOI: 10.1098/rspb.2006.3523
|View full text |Cite
|
Sign up to set email alerts
|

The coexistence of hybrid and parentalDaphnia: the role of parasites

Abstract: Parasite driven time-lagged negative frequency-dependent selection of hosts has been studied in natural populations by following changes in host genotype frequencies over time. However, such dynamics have not been considered at higher taxonomic levels, for example, between parental species and their hybrids. In a field study on a Daphnia hybrid system, we observed that one Daphnia taxon first was relatively underinfected, but became over-infected after a strong increase in frequency. This finding is consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
97
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(104 citation statements)
references
References 50 publications
6
97
1
Order By: Relevance
“…Parasites can play a regulatory function in host populations when the virulence of the parasite decreases the net growth rate of its host (Anderson and May 1981). Previous work established that C. mesnili decreases fecundity, growth, and life-span of its hosts Wolinska et al 2006), which we confirmed in the present study. Transmission likely occurs when naive hosts ingest spores during grazing.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Parasites can play a regulatory function in host populations when the virulence of the parasite decreases the net growth rate of its host (Anderson and May 1981). Previous work established that C. mesnili decreases fecundity, growth, and life-span of its hosts Wolinska et al 2006), which we confirmed in the present study. Transmission likely occurs when naive hosts ingest spores during grazing.…”
Section: Discussionsupporting
confidence: 89%
“…The parasite strain used for laboratory studies was collected in 2006 from a natural lake in Switzerland (Greifensee). The parasite was maintained in a D. galeata genotype collected from the same lake by adding newborns from uninfected stock cultures at approximately 2-week intervals (as described in Wolinska et al 2006). The daphniids were reared with an unlimited food supply of the unicellular green algae Scenedesmus obliquus in artificial medium (for details see Jeschke and Tollrian 2000).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specificity of host-parasite interactions was also shown to operate between groups of genotypes belonging to hybrid and parental taxa [12,13]. About 10 per cent of animal species are involved in hybridization and potential introgression [14].…”
Section: Introductionmentioning
confidence: 99%
“…There are several environmental factors influencing the fitness of Daphnia. Temperature (Weider and Wolf 1991), food level (Weider 1993), the predation regime (Spaak and Hoekstra 1997), and infections by parasites (Woliń ska et al 2006) have all been shown to alter the relative fitness of hybrids and parental species in the D. longispina complex. These factors vary in absolute strength and relative significance during the course of the year, ensuring a selective advantage of the hybrids under some conditions and of the parentals under other conditions.…”
mentioning
confidence: 99%